DISTRIBUTION OF MTHFR C677T GENE POLYMORPHISM IN HEALTHY NORTH MACEDONIAN POPULATION - Brezovska-Kavrakova, Julijana Marko; Trajkovska, Katerina Tosheska; Kostovska, Irena; Spasovski, Dejan; Petkovska, Lidija; Stratrova, Slavica Subevska (Journal of Morphological Sciences; Vol 4 No 2 (2021): JMS, 2021)
Methylenetetrahydrofolate reductase (MTHFR) is a key enzyme of folate pathway and mutation of the enzyme methylentetrahydrofolate reductase MTHFR C677T  gene. But whether it has influence on the level of total homocysteine is still under debate. Several polymorphisms have been reported in MTHFR gene, but C677T polymorphism is the most studied and it has been reported to be a risk factor for several diseases/disorders. Also, extensive studies have been conducted in various ethnic groups. The present study was designed to explore the frequency of MTHFR C 677T polymorphism in North Macedonian healthy population. The study group consisted of 123 healthy subjects, benevolent blood donors, who were declared to be healthy by a medical doctor from the National Institute for Transfusion Medicine in R.  N. Macedonia. The MTHFR gene polymorphism was analyzed by the polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP). Our analysis showed that the measurement of the population-genetic parameters of the allelic frequency at the T variable nucleotide had the allelic frequency 0.314. The global prevalence of TT genotype was Hardy - Weinberg's custom with a p value of 0.866, which was excluded from the x 2 test. The remaining parameters, however, indicated the genetically balanced population and they were important for the reliability of the analysis. In the Macedonian population T variant of the allele has the opposite frequency, but the lowest frequency has the genotype TT. Keywords : mutation of methylentetrahydrofolate reductase, frequency, Macedonian population   https://doi.org/10.55302/JMS2142035bk